Human and Mouse CD8+CD25+FOXP3+ Regulatory T Cells at Steady State and during Interleukin-2 Therapy - Churlaud, Guillaume; Pitoiset, Fabien; Jebbawi, Fadi; Lorenzon, Roberta; Bellier, Bertrand; Rosenzwajg, Michelle; Klatzmann, David (Frontiers in Immunology, 2015)
In addition to CD4+ regulatory T cells (Tregs), CD8+ suppressor T cells are emerging as an important subset of regulatory T cells. Diverse populations of CD8+ T cells with suppressive activities have been described. Among them, a small population of CD8+CD25+FOXP3+ T cells is found both in mice and humans. In contrast to thymic-derived CD4+CD25+FOXP3+ Tregs, their origin and their role in the pathophysiology of autoimmune diseases (AIDs) are less understood. We report here the number, phenotype and function of CD8+ Tregs cells in mice and humans, at the steady state and in response to low-dose interleukin-2 (IL-2). CD8+ Tregs represent approximately 0.4 and 0.1% of peripheral blood T cells in healthy humans and mice, respectively. In mice, their frequencies are quite similar in lymph nodes and the spleen, but 2- to 3-fold higher in Peyer patches and mesenteric lymph nodes. CD8+ Tregs express low levels of CD127. CD8+ Tregs express more activation or proliferation markers such as CTLA-4, ICOS, and Ki67 than other CD8+ T cells. In vitro, they suppress effector T cell proliferation as well as or even better than CD4+ Tregs. Owing to constitutive expression of CD25, CD8+ Tregs are 20- to 40-fold more sensitive to in vitro IL-2 stimulation than CD8+ effector T cells, but 2-4 times less than CD4+ Tregs. Nevertheless, low-dose IL-2 dramatically expands and activates CD8+ Tregs even more than CD4+ Tregs, in mice and humans. Further studies are warranted to fully appreciate the clinical relevance of CD8+ Tregs in AIDs and the efficacy of IL-2 treatment.